Java Sparrow Lonchura oryzivora at Bali Barat National Park: Do They Still Persist? - Mas Untung; Gde Oka Widiyavedanta; Egmont Congdenjit; Pramana Yuda; Luh Putu Eswaryanti Kusuma Yuni; I Made Saka Wijaya (Universitas Gadjah Mada, 2022)
The main purpose of the establishment Bali Barat National Park was to conserve the endemic endangered Bali Starling. However, based on data on 2004, one endangered species, Java Sparrow Lonchura oryzivora also resided in there. Current official report of sighting is ultimately required since it acts as reference in the management of a conservation area. We reported four sightings of Java Sparrow flocks occurred in June, 2021 at the Prapat Agung Peninsula, 28 individuals in total consisted of 13 adults and 15 juveniles, in a transition area of monsoon forest and savannah. The biggest flock sighted was eleven individuals. This study therefore confirmed that the Java Sparrow was still persisted at the Bali Barat National Park in 2021, in Prapat Agung Peninsula in particular.